Standard wide local excision or bilateral reduction mammoplasty in large-breasted women with small tumours: Surgical and patient-reported outcomes. Issue 4 (April 2017) - Di Micco, R.; O'Connell, R.L.; Barry, P.A.; Roche, N.; MacNeill, F.A.; Rusby, J.E.
Abstract: Introduction: Oncoplastic breast surgery is used to extend the role of breast-conserving surgery (BCS) to women with an unfavourable tumour to breast volume ratio. However, large-breasted women with a relatively small breast cancer may be offered bilateral reduction mammoplasty (BRM) despite being suitable for standard BCS as the more complex surgery may have advantages in terms of patient satisfaction and reduced adverse effects of radiotherapy. Patient and methods: This retrospective study evaluated surgical and patient-reported outcome measures (PROMs) in large-breasted women with early (<3 cm) breast cancer, who have undergone unilateral standard BCS or BRM. Results: This series included 157 women, 87 in the unilateral BCS group and 70 in the BRM group. Median age was 60.2 years (range: 33–83.9). Median follow-up was 36 months (range: 9.8–76). Tumour size, rates of axillary dissection, adjuvant chemotherapy and tumour bed irradiation boost were significantly greater in the BRM group ( p  < 0.05). The surgical complication rate was not significantly different (43.7% vs. 34.3%, p  = 0.253). Re-excision rates were higher in the standard BCS group ( p  < 0.05). Time to chemotherapy was similar, but time to radiotherapy was longer after BRM surgery ( p  = 0.025). Despite worse prognostic factors, more complex surgery and more aggressive adjuvant treatment, patients report better satisfaction and physical functioning and fewer adverse effects of radiotherapy after BRM than standard unilateral BCS. This difference was not statistically different in this small study ( p  > 0.05). Conclusion: Limitations of this study mean it can only be regarded as hypothesis-generating. Nonetheless, the trends merit a prospective study to investigate the optimal management of smaller breast cancers in larger-breasted women.